Gender issues in the Nigerian Armed Forces: A Literature Review - Yakubu, Funom Rapha (Corpus Intellectual, 2023)
In many societies, state security institutions have been created with the responsibility of defending a nation’s interest from both foreign aggressors and internal strife, and this responsibility has been placed in the hands of those who identify as masculine based on physiological, biological and social perceptions of what poses as strong as opposed to weak. Within the Security sector, several gender issues have been identified that are discriminatory in nature, favouring one gender group over another. In Nigeria especially, there is an underrepresentation of women in decisionmaking positions in the public sector and the trend stays true, especially across different security sector organisations. This paper, therefore engaged in an extensive review of literature, to understand the underpinnings of gender issues in the security sector, from an internal perspective focusing on the recruitment of female soldiers in the Nigerian Armed Forces, and the services offered to them in terms of quality of service rendered to arrive at its findings and draw up its conclusions. The study found out that although women are now employed as infantry and special forces fighters and the Nigerian Military Academy accepts women as cadets, it does not afford them the same training as their male colleagues and only a few of them will likely reach the pinnacle of the military complex. It, therefore, recommends that the Armed Forces of Nigeria adopt a range of supporting activities to encourage equitable chances in career development, including deployment for women as much as it does for men.